RANCANG BANGUN SISTEM INFORMASI PENERIMAAN SISWA BARU BERBASIS WEB PADA SDIT AL-IKHLAS - Iwan Jaya Iwan Jaya; Amat Suroso; Marhakim; Rizky Ramadhan (JURNAL ILMIAH BETRIK : Besemah Teknologi Informasi dan Komputer, 2022)
SDIT Al-Ikhlas is a company or organization that is engaged in education and has the aim of building moral and moral citizens of the country. There are several problems that sometimes arise at SDIT Al Ikhlas when accepting prospective students including SDIT Al-Ikhlas which has not implemented web-based student admissions, so admissions are still done offline using paper-shaped forms which are certainly time consuming and less efficient. Leaders who only receive reports when the process of accepting new students has been completed, and the report is still in the form of paper which is of course easily damaged or lost and difficult to find when needed. The use of the system in accepting prospective students is very helpful for SDIT Al-Ikhlas as well as prospective students and their parents in registering. Therefore, the authors design and create a system to accept new students and the waterfall method is used to develop the system, because this method has a clear flow so as to minimize errors so as to speed up the development process. With this system the above problems will be overcome, this system was built to help especially the school in implementing activities to accept prospective students